Oocyte accumulation for fertility preservation in women with benign ovarian tumours with a history of previous surgery, multiple or large cysts. Issue 2 (August 2021) - Legrand, Charlotte; Keller, Laura; Collinet, Pierre; Barbotin, Anne Laure; Béhal, Hélène; Rubod, Chrystele; Decanter, Christine
Abstract: Research question: What are ovarian stimulation cycle outcomes and acceptance rates of an oocyte accumulation programme in young women with benign ovarian tumour (BOT)? Design: Retrospective cohort study conducted at the Academic Assisted Reproductive Technology and Fertility Preservation Centre, Lille University Hospital, between January 2016 and December 2019. The number of metaphase II oocytes per cycle and per patient after accumulation were evaluated. Two groups were identified for the analysis: endometrioma ('endometrioma') and dermoid, mucinous or serous cyst ('other cysts'). Results: A total of 113 fertility-preservation cycles were analysed in 70 women aged 27.9 ± 4.8 years. Almost all women had undergone previous ovarian surgery before fertility preservation (89%). Mean anti-Müllerian hormone levels before ovarian stimulation was 12.5 ± 8.7 pmol/l. A total of 6.4 ± 3.4 oocytes were retrieved, and 4.3 ± 3.4 metaphase II (MII) oocytes were vitrified per cycle. All agreed to the oocyte accumulation programme and all underwent at least one cycle. To date, 36 (51%) patients achieved two or three fertility- preservation cycles. After accumulation, 7.0 ± 5.23 MII oocytes were vitrified per patient. No difference was found in ovarian response and oocyte cohort between the 'endometrioma' and 'other cysts' groups. Questionnaires completed after oocyte retrieval revealed abdominal bloating and pelvic pain in most patients, with no difference according to the type of cyst. No serious adverse events occurred. Conclusions: Oocyte accumulation should be systematically offered to young women with BOT irrespective of histological type, as it seems to be well-tolerated. Long-term follow-up is needed to assess the efficiency of oocyte accumulation to optimize the chances of subsequent pregnancies.